Animal model for progressive resistance exercise: a detailed description of model and its implications for basic research in exercise Modelo animal de exercício resistido progressivo: descrição detalhada do modelo e a sua implicação à pesquisa básica com exercício - Ricardo Cardoso Cassilhas; Ismair Teodoro Reis; Daniel Venâncio; Jansen Fernandes; Sérgio Tufik; Marco Túlio de Mello (Universidade Estadual Paulista (UNESP), 2013)
The Several animal models have been proposed for resistance training. In addition, the results of these studies have been highly variable. Some of the studies have used negative reinforcement, electric shock or food deprivation to motivate the learning of the task. Features such as conditioning through electric shock may undermine the significance of the results or even prevent the model from being successfully executed. Due to these reasons, in this study we propose to use an adaptation of the vertical ladder climbing model for progressive resistance training in rats, albeit with a unique feature to ensure the homogeneity of the study groups: a period of adaptation to the apparatus without any negative reinforcement followed by a subsequent pairing of animals based on their ability to learn. The animals were distributed in the experimental group who were subjected to 8 weeks of a progressive resistance exercise protocol and the control group. After 8wks, the gastrocnemius, soleus, flexor digitorum longus (FDL), and plantaris muscles were removed and the cross-sectional area morphometry was obtened. The animals from experimental group showed hypertrophy [F(4, 15)=17,404, P < 0.001] for gastrocnemius [60% of hipertrophy; Control (2628,64 ± 348,50) versus Experimental (4207,77 ± 1256,52); ES=1.96; Power=0,86]; FDL [35% of hipertrophy; Control (2753,80 ± 359,54) versus Experimental (3711,84 ± 279,45); ES=2.99; Power=0.99] and plantaris [38% of hipertrophy; Control (2730,44 ± 320,56) versus Experimental (3767,30 ± 625,80); ES=2.19; Power=0.92], without modifications for soleus. All animals successfully completed the 8-week progressive resistance training program without any injuries, abandonment or death. Negative reinforcements such as electric shock were not required at any time in the experiment. In conclusion, we showed an adaptation of the previus model for progressive resistance training in rats. A period of adaptation to the apparatus without any negative reinforcement followed by a subsequent pairing of animals based on their ability to learn may be a alternative strategy for the original protocol. We also observed hypertrophy (gastrocnemius, FDL, and plantaris) showed the vality of this procolos for resistance exercise issues. The results of this study may be useful in basic/ applied neuroscience research and resistance exercise. Alguns modelos animais de treinamento resistido vem sendo proprostos ao longo do tempo, com resultados variáveis e por vezes conflitantes. Contudo, todos eles utilizam reforço negativo ao ensinar os animais o aprendizado da tarefa, por exemplo, choque elétrico ou privação alimentar e tais condicionamentos podem interferir de algma forma na variável estudada. Por estas razões, este estudo propões uma adaptação de um modelo de treinamento resistido de subida em escada vertical já existente, mas com um período de familiarização ao equipamento, sem choque elétrico, seguido pela distribuição de acordo com o desempenho do aprendizado de subida em escada. Os animais foram distribuídos em: grupo experimental (submetido a oito semanas de treinamento resistido) e grupo controle. Após a intervenção, os músculos gastrocnemius, soleus, flexor digitorum longus (FDL), and plantaris foram removidos e a moformetria das fibras muculares foi realizada. Os animais do grupo experimental mostraram hipertrofia [F(4, 15)=17,404, P < 0.001] nos músculos: gastrocnemius [60% de hipertrofia; Control (2628,64 ± 348,50) versus Experimental (4207,77 ± 1256,52); ES=1.96; Power=0,86]; FDL [35% de hipertrofia; Control (2753,80 ± 359,54) versus Experimental (3711,84 ± 279,45); ES=2.99; Power=0.99] e plantaris [38% de hipertrofia; Control (2730,44 ± 320,56) versus Experimental (3767,30 ± 625,80); ES=2.19; Power=0.92], sem alterações no soleus. Ainda, todos os animais completaram o protocolo sem qualquer lesão, abandono ou morte. Reforço negativo como choque elétrico ou de outra natureza não foi realizado por todo o experimento. Concluindo, foi mostrado uma adaptação de modelo de treinamento resistido progressivo em ratos. Um período de adaptação ao aparato sem qualquer reforço negativo somado a um período de adaptação baseado na distribuição de acordo com o desempenho do aprendizado de subida em escada, pode ser uma estratégia ao protocolo original. Foi mostrado também hipetrofia (gastrocnemius, FDL, and plantaris) o que mostra a validade deste protocolo para o treinamento resistido. Os resustados do presente podem ser utilizados em pesquisa sobre neurociências básica/ aplicada e exercício resistido.